No Effect of Inversion on Attentional and Affective Processing of Facial Expressions - Lipp, Ottmar; Price, S.; Tellegen, C. (American Psychological Association, 2009)
The decrease in recognition performance after face inversion has been taken to suggest that faces are processed holistically. Three experiments, 1 with schematic and 2 with photographic faces, were conducted to assess whether face inversion also affected visual search for and implicit evaluation of facial expressions of emotion. The 3 visual search experiments yielded the same differences in detection speed between different facial expressions of emotion for upright and inverted faces. Threat superiority effects, faster detection of angry than of happy faces among neutral background faces, were evident in 2 experiments. Face inversion did not affect explicit or implicit evaluation of face stimuli as assessed with verbal ratings and affective priming. Happy faces were evaluated as more positive than angry, sad, or fearful/scheming ones regardless of orientation. Taken together these results seem to suggest that the processing of facial expressions of emotion is not impaired if holistic processing is disrupted. © 2009 American Psychological Association.